Estimasi Kebutuhan Ruang Terbuka Hijau (RTH) Berdasarkan Urban Heat Island (UHI) di Kota Semarang - Astuti, Widi; Putri, Bunga Ludmila Rendrar; Anwar, Khoirul; Yanti, Novi; Pambudi, Puguh (Badan Riset dan Inovasi Daerah Kota Semarang, 2022)
The city of Semarang has experienced a decline in environmental quality due to its various activities. The dense population with a consumptive lifestyle has a negative impact on the environment. The green open space area of Semarang City has fulfilled the percentage of green open space area in accordance with the Regulation of the Minister of Agrarian and Spatial Planning/Head of the National Land Agency Number 14 of 2022. However, in terms of quality and quantity this fulfillment has not been achieved because the distribution is uneven in the 16 sub-districts of Semarang City. This study aims to identify the distribution needs of UHI and the area of green space distribution in Semarang City. The method in this research is descriptive research with the data analysis method carried out using Arcgis software. Quantitative data analysis is carried out by calculating the area of green open space and UHI using Landsat 8 imagery in 2016, 2019 and 2021. The results of this study are a decrease in building density (NDBI) in the non-building category from 2016 to 2021 of 4.6% or an area of 1800.26 ha. The increase in the area that occurred in the sparse vegetation category from 2016 to 2019 was accompanied by a decrease in the area of the dense vegetation category from 26.03% to 18.96%.